Level of physical activity in elderly women - Nelyse de Araújo Alencar; Márcia de Assunção Ferreira; Rodrigo Gomes de Sousa Vale; Estélio Henrique Martin Dantas (Universidade de Fortaleza, 2011)
Objective: To assess physical activity levels (PAL) in elderly women practitioners of physical activity followed-up by a Family Health team of the city of Crato-CE, Brazil. Methods: To determine the level of physical activity, we used the Modified Baecke Questionnaire for Elderly (MBQE). In the statistical evaluation of obtained differences we applied the Student t test, with a significance level of p <0.05 and size-effect. Results: Comparing the level of physical activity, according to the MBQE classification, of the women who practiced walking (67.2% of the total, PAL = 4.45, classified as high) with those who performed only domestic activities (54.1%, PAL = 1.71, low), we observed a D% = 160%, 24%, p <0.001. The Conhen index that expresses the magnitude of this difference was 6.23 (high). Conclusion: According to the results, it is inferred that the practice of regular physical activity such as walking, can improve the levels of motor activity in elderly.